2020
DOI: 10.1016/j.mtphys.2020.100263
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-high critical electric field of 13.2 MV/cm for Zn-doped p-type β-Ga2O3

Abstract: high critical electric field of 13.2 MV/cm for Zn-doped p-type ß-Ga2O3. Materials Today Physics, (2020).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 43 publications
0
24
0
Order By: Relevance
“…Ultra-wide bandgap (UWBG) semiconductor oxides have recently rejuvenated [1,2] and are now attracting considerable interest as an advanced platform for energy electronics, including deep UV optoelectronics and power devices owing to their ultra-high critical electric field [3], control of the electrical conductivity, chemical stability and the possibility of grown large single crystals (up to 6-inch) at a reduced cost (i.e., Silicon-like Czochralski (CZ) method) [4]. The binary oxide semiconductor gallium oxide (Ga2O3) (Egap ~4.6-4.9 eV) is somehow heralding this emerging field, but complex gallium oxide alloys are widely investigated in particular Ga2O3:Al2O3 [5] and Ga2O3:ZnO [6].…”
Section: Introductionmentioning
confidence: 99%
“…Ultra-wide bandgap (UWBG) semiconductor oxides have recently rejuvenated [1,2] and are now attracting considerable interest as an advanced platform for energy electronics, including deep UV optoelectronics and power devices owing to their ultra-high critical electric field [3], control of the electrical conductivity, chemical stability and the possibility of grown large single crystals (up to 6-inch) at a reduced cost (i.e., Silicon-like Czochralski (CZ) method) [4]. The binary oxide semiconductor gallium oxide (Ga2O3) (Egap ~4.6-4.9 eV) is somehow heralding this emerging field, but complex gallium oxide alloys are widely investigated in particular Ga2O3:Al2O3 [5] and Ga2O3:ZnO [6].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, an ultra-large breakdown electric field, (which is usually assumed to be of the order of E c ~8 MVcm −1 ), is a prime material advantage of Ga 2 O 3 . However, this value may be well underestimated; it was very recently suggested that the critical electric field of Ga 2 O 3 could be as large as 13.2 MVcm −1 , if the residual donors are efficiently removed [ 24 ].…”
Section: Gallium Oxide (Ga 2 O 3 )mentioning
confidence: 99%
“…The growth rate is generally from several hundred nm/h [ 100 , 101 ] to10 µm/h [ 102 , 103 , 104 ]. This technique is also available for both n - and p -type dupability [ 24 , 105 ] ( Figure 4 ).…”
Section: Gallium Oxide (Ga 2 O 3 )mentioning
confidence: 99%
“…[29] Moreover, Zn doping has been demonstrated to enhance critical electrical field up to 13.2 MV cm À1 in MOVPE grown β-Ga 2 O 3 . [30] In view of aforementioned facts, the development of Zn doping processes in epitaxial growth of β-Ga 2 O 3 is strongly motivated.…”
Section: Introductionmentioning
confidence: 99%